Buniyaad: Foundation for a healthy child - Singh, Abhishek (International Food Policy Research Institute, 2015)
In October 2012, a baseline survey conducted in 20 blocks in the districts of Muzaffarpur, Samastipur, and Sitamarh in Bihar found significant gaps in infant and young child feeding (IYCF) practices, such as a low rate of breastfeeding immediately following delivery and the absence of any feeding schedule for children (Aga Khan Foundation 2012).